McCarthyism : the great American Red Scare ; a documentary history - Fried, Albert (Oxford Univ. Press, 1997)
Drawing upon a rich selection of documents, this text provides a detailed account of McCarthyism and the American Red Scare, a period which spanned from the late 1940s to the mid 1960s. It discusses the turbulent years during which Americans were routinely persecuted because they were suspected of being insufficiently patriotic or too sympathetic to the Soviet Union. The persecution took various forms, from imprisonment to the purging and blacklisting of untold thousands. Fried demonstrates how the end result was to consign the American radical left to irrelevancy, helping to ensure that already established policies, both foreign and domestic, would remain unchallenged. Fried provides informative introductions and head notes for each section, as well as a useful bibliography. Through speeches, executive orders, congressional hearings, court decisions, official reports, letters, memoirs, and essays, this text offers the most sweeping and comprehensive look at McCarthyism, highlighting the cruelty, poignancy, and absurdity of this extraordinary period of time. Documenting both the persecuted and the persecutors, this is the definitive reader and core text for courses on McCarthyism, and an ideal supplement for courses on American history and political science